LAGGING OF INDUSTRIES IN WEST BENGAL & ITS EFFECT ON UNEMPLOYMENT - Mandal, Jayanta (AGPE THE ROYAL GONDWANA RESEARCH JOURNAL OF HISTORY, SCIENCE, ECONOMIC, POLITICAL AND SOCIAL SCIENCE, 2023)
Employment is considered to be one of the main contributors to the progress of human life. Employment is known as one of the main pillars of livelihood in modern times. With employment, the youth find a way to establish themselves. Industrialization is one of the easiest ways to create employment in the modern large-scale state system. Although there is a livelihood opportunity in the unorganized sector, the guarantee of employment is created through industrialization. It is not observed in any other case. The relationship between industrialization and employment is eternal. In the era of modern industrialization, employment is largely dependent on factories. Industrialization progress started soon after Indian colonial rule. Bihar, Jharkhand, Orissa, including West Bengal, it did not take long to create an industrial environment. Answer: Colonial West Bengal depended mainly on jute industry. Later industries like iron, mica, electrical manufacturing etc. started flourishing. There is not much news about the industrialization progress of West Bengal in recent times. On the contrary, due to the closure of factories one after the other, the way of employment has been blocked for the youth of West Bengal. Statistics show that the trend of government jobs has decreased day by day, especially since 2000, when the growing industrial establishment in West Bengal became the biggest hope of employment for the youth. But at present the government’s policy is in a state of wavering hope and fear due to various reason such as land related complications. In this situation, it is considered that a sufficient range of thinking about employment has been created. I intend to discuss in my research paper the situation of industrialization, employment prospects and consequences of unemployment.